Efficacy and safety of ureterorenoscopy in the elderly: A systematic review axnd meta-analysis - Minna Shen; Minqiang Shen (PLoS ONE, 2025)
Objective Ureterorenoscopy (URS) is a common procedure performed for renal or upper ureteric stones. Nevertheless, the efficacy and safety of URS in the elderly is unclear. We conducted the first meta-analysis of literature comparing outcomes of URS between elderly and non-elderly patients. Methods Embase, PubMed, Web of Science, and Scopus databases were searched for studies relevant to the review. The last date was 2nd September 2024. The elderly were defined as ≥ 65 or 60 years of age. Outcomes compared were stone-free rates (SFR), complications, and length of hospital stay (LOS). Results Nine studies met the inclusion criteria. Pooled analysis showed that there was no difference in SFR between elderly and non-elderly groups after URS (OR: 0.96 95% CI: 0.81, 1.14 I2 = 3%). Meta-analysis failed to show any statistical significant in all complication rates (OR: 1.04 95% CI: 0.77, 1.40 I2 = 51%) as well as infectious (OR: 1.27 95% CI: 0.84, 1.92 I2 = 0%), medical (OR: 2.01 95% CI: 0.23, 17.57 I2 = 93%), surgical (OR: 1.18 95% CI: 0.68, 2.03 I2 = 0%) or Clavein Dindo grade ≥2 (OR: 1.02 95% CI: 0.60, 1.75 I2 = 0%) complications between elderly and non-elderly groups. Meta-analysis showed that the elderly had significantly longer LOS as compared to non-elderly patients (MD: 0.75 95% CI: 0.05, 1.45 I2 = 90%). Conclusions URS seems to efficacious and safe in the elderly. Patients ≥60 or 65 years of age have similar SFR and complication rates as younger patients. However, LOS may be increased in the elderly. More robust studies taking into account baseline characteristics and importantly presenting rates are needed to validate the current results.